Status epilepticus as a complication after COVID-19 mRNA-1273 vaccine: A case report - Šín, Robin; Štruncová, Denisa (World journal of clinical cases, 2021)
BACKGROUND: We present a rare case of status epilepticus in a 56-year-old man which arose as a complication after vaccination with the coronavirus disease 2019 (COVID-19) mRNA-1273 vaccine. The patient's history included well-compensated secondary epilepsy. The root cause of the situation was a fever which had developed as a side effect of the vaccination. CASE SUMMARY: A 56-year-old man received the first dose of mRNA-1273 vaccine against the severe acute respiratory syndrome-coronavirus-2. The vaccine was administered intramuscularly (100 mg, 0.5 mL). The next morning the man was found to be suffering from fever and headaches while at the same time experiencing general weakness. He lost consciousness suddenly and experienced generalized clonic seizures which turned into status epilepticus. When the Emergency Medical Service arrived the patient was unconscious with spontaneous breathing and generalized clonic seizures. It was necessary to administer diazepam repeatedly. It was also necessary to administer high doses of levetiracetam and temporary propofol. The status epilepticus was brought under control approximately 90 min after the patient's transport to the Emergency Department. A follow-up electroencephalogram no longer revealed abnormal indications of epileptic fit. The patient was temporarily hospitalized in the Intensive Care Unit and after seven days care was discharged without any further apparent effects. CONCLUSION: There is currently no specific treatment against COVID-19. Therefore, the benefits of COVID-19 vaccine protection outweigh the risks.